Cognitive behavior therapy untuk menurunkan gejala gangguan cemas menyeluruh pada remaja - Ningsih, Windar; Hidayati, Erny (Universitas Muhammadiyah Malang, 2024)
Generalized anxiety disorder is characterized by excessive and uncontrollable anxiety, worrying about various events and activities. The symptoms that the subject agitated, anxious or tense, unable to stop or control the worry, having difficulty relaxing, and feeling afraid something terrible might happen. The subject is a 15 year old who was a victim of bullying. The aim of this case study is to reduce the symptoms of generalized anxiety disorder through cognitive behavioral therapy. The data collection methods used were interviews, observation and psychological tests. The intervention was cognitive behavior therapy with mind over mood techniques. The aim of the intervention to change his cognitive distortions and develop positive thoughts. The results of the intervention showed that cognitive behavior therapy was effective in reducing the symptoms of generalized anxiety disorder, which was marked by a decrease in the GAD-7 score from 18 to 8. Gangguan kecemasan umum ditandai dengan rasa cemas yang berlebihan dan tidak terkendali, khawatir terhadap berbagai kejadian dan aktivitas. Gejalanya yaitu subjek gelisah, cemas atau tegang, tidak mampu menghentikan atau mengendalikan rasa khawatir, sulit bersantai, dan merasa takut akan terjadi sesuatu yang buruk. Subyeknya adalah seorang remaja berusia 15 tahun yang menjadi korban bullying. Tujuan dari studi kasus ini adalah untuk mengurangi gejala gangguan kecemasan umum melalui terapi perilaku kognitif. Metode pengumpulan data yang digunakan adalah wawancara, observasi dan tes psikologi. Intervensi yang dilakukan adalah terapi perilaku kognitif dengan teknik mind over mood. Tujuan intervensi untuk mengubah distorsi kognitifnya dan mengembangkan pikiran positif. Hasil intervensi menunjukkan terapi perilaku kognitif efektif mengurangi gejala gangguan kecemasan umum yang ditandai dengan penurunan skor GAD-7 dari 18 menjadi 8.